Probucol promotes osteoblasts differentiation and prevents osteoporosis development through reducing oxidative stress - Zhou-Shan Tao; Tian-Lin Li; Shan Wei (Molecular Medicine, 2022)
Abstract Probucol (PBC) is a potent cholesterol-lowering drug and has been studied extensively for its powerful antioxidative stress. The purpose of this study is to investigate the role of PBC in ovariectomized rat model and to explore the mechanism of osteogenic differentiation of MC3TE-E1 Cells. RT-qPCR and Immunofluorescence were used to measure the expression level of SOD2, SIRT1, intracellular oxidative stress levels and osteogenic markers proteins. Moreover, CCK-8 assay was conducted to detect cell viability. Alizarin red staining and alkaline phosphatase staining were applied to examine osteogenic function and calcium deposits. The ovariectomized rat model was set up successfully and HE staining were employed to examine femoral trabeculae tissue. Our results showed that PBC suppressed MC3TE-E1 resist oxidative stress to promote osteogenic differentiation. Additionally, it was confirmed that PBC promoted osteogenic differentiation of MC3TE-E1 through inhibiting oxidative stress. Further study indicated that PBC exerted its beneficial function by suppressing oxidative stress-mediated alter bone metabolism to alleviate osteoporosis in vivo. Our research suggested that the PBC-modulated oxidative stress inhibition is responsible for activation of the process of osteogenic differentiation, providing a novel insight into the treatment of osteoporosis. Graphical abstract